2020
DOI: 10.3389/fmicb.2020.575563
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Symbionts Enhance N-Uptake for Antarctic Plants Even in Non-N Limited Soils

Abstract: Acuña-Rodríguez et al. N-Uptake Modulated by Endophytes under rich N soils, the two Antarctic vascular plants showed that the presence of rootfungal endophytes, furthermore enhanced the availability of inorganic N sources in the rhizosphere, has a positive impact in their biomass, remarking the active participation of these endophytes in the N-uptake process for plants inhabiting the Antarctic continent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…More N in the soil, for example, can be attributed to a higher urease activity, which is increased in moister soils ( Delgado-Baquerizo et al, 2015 ; Liu et al, 2016 ), such as those with the presence of BSCs. The biological nitrogen mineralization process could also be positively influencing the levels of available nitrogen, which could be mediated by microbial activity, as seen in other studies ( Acuña-Rodríguez et al, 2020 ), mainly attributed to fungi that could be also present in the BSCs. Moreover, leaf nutrient content was higher on C. quitensis plants exposed to BSCs compared to plants grown only in BS.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…More N in the soil, for example, can be attributed to a higher urease activity, which is increased in moister soils ( Delgado-Baquerizo et al, 2015 ; Liu et al, 2016 ), such as those with the presence of BSCs. The biological nitrogen mineralization process could also be positively influencing the levels of available nitrogen, which could be mediated by microbial activity, as seen in other studies ( Acuña-Rodríguez et al, 2020 ), mainly attributed to fungi that could be also present in the BSCs. Moreover, leaf nutrient content was higher on C. quitensis plants exposed to BSCs compared to plants grown only in BS.…”
Section: Discussionmentioning
confidence: 67%
“…In the case of Antarctic terrestrial ecosystems, two native vascular plants, Deschampsia antarctica and Colobanthus quitensis , coexist as dominant elements, along with a mosaic of different BSCs ( Molina-Montenegro and Cavieres, 2010 ; Parnikoza et al, 2011 ). While both plants grow successfully in the Antarctic tundra, their ecological strategies vary greatly; D. antarctica has several physiological traits that allow it to survive the extreme conditions of Antarctica ( Sáez et al, 2019 ), but C. quitensis seems to strongly depend on mutualistic interaction with microorganisms ( Torres-Díaz et al, 2016 ; Gallardo-Cerda et al, 2018 ; Acuña-Rodríguez et al, 2020 ). Thus, we believe that it is highly important to describe the composition of Maritime Antarctic BSCs (King George Island, South Shetland Islands) and their effect on the physical–chemical properties of the soil, and to evaluate their effect on the ecophysiological performance of Colobanthus quitensis .…”
Section: Introductionmentioning
confidence: 99%
“…The color was only affected in fruits obtained from inoculated and well-watered plants, in which a moderate but statistically significant increase in the lightness was observed compared to the other treatments. These results could be explained by the role of Antarctic fungal endophytes to enhance nutrient uptake, including nitrogen and phosphorus ( Newsham, 2011 ; Acuña-Rodríguez et al, 2020 ). The symbiotic interactions increase the availability of essential nutrients for the synthesis of amino acids and proteins in the host plants ( Harman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The endophytes, which had been isolated from surface‐sterilised root fragments of each plant species, were identified through sequencing of the partial internal transcribed spacer region and large subunit genes (Torres‐Díaz et al, 2021). Previous studies have shown that each of the six isolates colonises the roots of lettuce ( Lactuca sativa ), tomato ( Solanum lycopersicum ) and bell pepper ( Capsicum annuum ) grown in monoculture (Acuña‐Rodríguez et al, 2019; Molina‐Montenegro et al, 2016, 2020), with hyphae growing on root surfaces and apoplastically between epidermal cells (Acuña‐Rodríguez et al, 2020).…”
Section: Methodsmentioning
confidence: 99%